An Appraisal of the Role Played by State Courts in Combating Medical Negligence in Cameroon: A Review of Selected Case Laws - Agbor James Eyong (Studies in Law and Justice, 2025)
This paper critically appraises the role of state courts in combating medical negligence in Cameroon through a review of selected judicial decisions. The research adopts a qualitative methodology, relying on doctrinal analysis and case study approaches to explore the effectiveness, consistency and limitations of judicial responses to medical negligence and malpractices. By examining a purposively selected sample of landmark cases from Cameroonian courts, the study assesses how legal principles are interpreted and applied, the adequacy of judicial remedies and the broader implications for patients’ rights and healthcare accountability. The findings reveal a gradual, yet uneven evolution in judicial attitudes towards medical negligence, marked by procedural delays, limited expertise in medical matters and inadequate enforcement of judgments. The paper concludes that while courts have an essential role in promoting accountability and deterrence, there is a pressing need for judicial reforms, capacity building and enhanced legal frameworks to ensure justice for victims of medical negligence in Cameroon.